2014
DOI: 10.32677/ijch.2018.v05.i01.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a simplified gestational age score in low birth weight newborns in India

Abstract: Background: Assessment of gestational age (GA) based on the last date of menstrual period is often inaccurate. Scores to predict GA of newborns are difficult to use particularly by health workers. An accurate, easy to use the method of assessing GA, particularly in low birth weight (LBW) babies, is needed to detect and link premature newborns to the appropriate level of care. Objectives: The objectives were (1) to develop a "simplified GA score" (SGAS) by selecting items from 3 standard GA scores that signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thirdly, we used the dichotomous categorizations of preterm obtained from the two assessments and estimated Fleiss's kappa on this dichotomous classification. Our previous studies have shown that a score of 14 or more is indicative of a term baby [9]. This cut-off was used to generate the dichotomous categories from the two assessments.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, we used the dichotomous categorizations of preterm obtained from the two assessments and estimated Fleiss's kappa on this dichotomous classification. Our previous studies have shown that a score of 14 or more is indicative of a term baby [9]. This cut-off was used to generate the dichotomous categories from the two assessments.…”
Section: Plos Onementioning
confidence: 99%
“…T-SGAS is simple with just a simple 4 item scoring scale with 3 physical and 1 neurological item. T-SGAS was developed by using the most predictive items from the 12-item New Ballard Score (NBS), 22-item Dubowitz score (DWS) and 11-item Meharban Singh (MS) and validated against the Best obstetrics Estimate (BOE) in low birth weight (LBW) newborns in India [9]. Because it showed promising results for estimation of GA in LBW newborn and was easy to by nursing staff in the community it was adapted to a pictorial tablet app (T-SGAS) [8].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We previously used the NBS, DWS and Meharban Singh scoring system to develop a 4-item simplified gestational age score (SGAS) for use in low birth weight newborns in India [ 13 ]. The 4-item scoring system is as follows: posture (0 to 4), skin (–1 to 5), breasts (–1 to 4), and genitals (–1 to 4).…”
Section: Introductionmentioning
confidence: 99%
“…The total score was used to define 4 SGAS categories: <32 weeks, ≥32 to <35 weeks, ≥35 to <37 weeks, and ≥37 weeks. The SGAS then underwent initial testing in 171 newborns [ 13 ] and was found to have a high positive predictive value for very preterm (<32 weeks gestation) and moderate preterm (32-35 weeks gestation) neonates compared with the NBS. In our prior study, a score of <14 predicted that a newborn was preterm (GA of <37 weeks).…”
Section: Introductionmentioning
confidence: 99%